Transportation Laws for Carbonate and Sulfate Ions in Concrete Based on Compartment Model - Boxin Wang; Ruichang Fang; Xu Chai; Qing Wang (Advances in Civil Engineering)
Transportation of carbonate and sulfate ions in concrete under the drying-wetting cycle environment is similar to the ingression and elimination of medicine in human body. Given this similarity, such a process is described dynamically using the classic compartment model in pharmacokinetics. The compartment model was applied to predict the content of carbonate and sulfate ions in different regions of concrete. Factors such as water-cement ratio, salt category, carbonate-ion and sulfate-ion attack depth, and drying-wetting cycle were synthetically considered in the compartment model. In conjunction with the prediction value of the compartment model, the experiment data uniformly distributed two sides of the model curve, and the difference is within the accepted range, thus verifying the reliability of the model prediction consequence. The compartment model in this article provides references for predicting the drying-wetting varied cycles and ions attack depth of concrete under carbonate and sulfate ions attack.